Native Oxide Barrier Layer for Selective Electroplated Metallization of Silicon Heterojunction Solar Cells. Issue 6 (27th March 2019) - Hatt, Thibaud; Kluska, Sven; Yamin, Mananchaya; Bartsch, Jonas; Glatthaar, Markus
Abstract : The metallization of silicon heterojunction (SHJ) solar cells by electroplating of highly conductive copper onto a multifunctional patterned metal layer stack is demonstrated. The approach features several advantages: low temperature processing, high metal conductivity of plated copper, no organic making, and low material costs (almost Ag‐free). A PVD layer stack of copper and aluminum is deposited onto the cell subsequently to TCO deposition. The aluminum layer is patterned with a printed etchant and its native oxide on the remaining areas inhibits plating. The full area aluminum layer while electroplating supports plating current distribution and allows homogeneous plating height distributions over the cell. The NOBLE (native oxide barrier layer for selective electroplating) approach allows reaching a first encouraging SHJ solar cell efficiency of 20.2% with low contact resistivity. Abstract : The metallization of silicon heterojunction (SHJ) solar cells by simultaneous bifacial electroplating of highly conductive copper onto a multifunctional patterned metal layer stack is demonstrated. The NOBLE (native oxide barrier layer for selective electroplating) approach allows reaching a first encouraging efficiency of 20.2% with low contact resistivity on a lab‐scale SHJ solar cell.